Communication and trust in principal-team relationships: Experimental evidence - Marco Kleine; Sebastian Kube (Max Planck Institute for Research on Collective Goods, 2015)
We study how upward communication - from workers to managers - about individual efforts affects the effectiveness of gift exchange as a contract-enforcement device for work teams. Our findings suggest that the use of such self-assessments can be detrimental to workers performance. In the controlled environment of a laboratory gift-exchange experiment, our workers regularly overstate their own contribution to the joint team output. Misreporting seems to spread distrust within the team of workers, as well as between managers and workers. This manifests itself in managers being less generous with workers payments, and in workers being more sensitive to the perceived kindness of their relative wage payments. By varying the source and degree of information about individual efforts between treatments, we see that precise knowledge about workers actual contributions to the team output is beneficial for the success of gift-exchange relationships. Yet, workers self-assessments can be a problematic tool to gather this information.
Keywords: J33; C92; M52; 330; reciprocity; incomplete contracts; communication; laboratory experiment; gift exchange; performance appraisal; self-assessment; work team